Reversible intramyelinic cytotoxic edema in a patient with traumatic brain injury - Barragán, Catalina; González-Gómez, Silvia; Barrera, Adriana; Soler, Camilo (Neurological sciences, 2025)
We report a case demonstrating magnetic resonance imaging findings of reversible white matter restriction on diffusion-weighted imaging and apparent diffusion coefficient maps in a patient with traumatic brain injury. A 22-year-old man presented to the emergency department following a severe motor vehicle collision. The magnetic resonance imaging revealed multiple focal hemorrhagic contusions, supratentorial diffuse axonal injury, a left parietotemporal subdural laminar hematoma, and extensive diffusion restriction on diffusion coefficient maps involving the deep white matter of the centrum semiovale bilaterally, as well as the splenium of the corpus callosum. The patient was hospitalized, and follow-up magnetic resonance showed a complete resolution of the diffusion-restricted areas. This case illustrates a traumatic brain injury associated with transient, reversible intramyelinic cytotoxic edema.